Islam and Science: The Philosophical Grounds for a Genuine Debate - Khani, Ali Hossein (Zygon, 2020)
What does it take for Islam and science to engage in a genuine conversation with each other? This essay is an attempt to answer this question by clarifying the conditions which make having such a conversation possible and plausible. I will first distinguish between three notions of conversation: the trivial conversation (which requires sharing a common language and the meaning of its ordinary expressions), superficial conversation (in which although the language is shared, the communicators fail to share the meaning of their theoretical terms), and genuine conversation (which implies sharing the language and the meaning of ordinary as well as theoretical terms). I will then argue that our real concern with regard to the exchange between Islam and science is to be to specify the conditions under which their proponents can engage in a genuine conversation with each other and that such a conversation to take place essentially requires sharing a common ontology. Following Quine, I will argue that Muslims, like the followers of any religion, would have no other choice but to work from within science. Doing so, however, would not prevent Muslims from having a genuine conversation with the proponents of other worldviews because when the shared ontology fails to offer any potentially testable answer to our remaining questions about the world, the Islamic viewpoint can appear as a genuine alternative among other underdetermined ones, deciding between which would be a matter of pragmatic criteria.